2016
DOI: 10.1155/2016/2492450
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of TSHR, TTF-1, and PAX8 in Nodular Goiter Is Associated with Iodine Deficiency in the Follicular Lumen

Abstract: Objective. It has been testified that iodine regulates thyroid function by controlling thyroid-restricted genes expression and is closely related to diffuse goiter and thyroid dysfunction. However, the effects of follicular lumen iodine, the main form of iodine reserve in the body, on thyroid-restricted genes in nodular goiter are poorly understood. In this study, correlations between follicular lumen iodine and the expressions of thyroid stimulating hormone receptor (TSHR), its transcription factors TTF-1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Another limitation is the small number of included patients, especially those with Wagner-Meggit grade 1 or IWGDF/IDSA grade 1 wound, and rarely neuropathic ulcerations. Tissue biopsy is known as the most standard method, and swab cultures are considered as not reliable since it generally includes the colonizers and not the causative pathogen [ 15 ]. But in this study, the swabs were obtained after a complete debridement in order to avoid the colonizers, and the CNS, as the main colonized organisms in the skin, were detected lower than 10% in this study, which showed that the swabs were reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is the small number of included patients, especially those with Wagner-Meggit grade 1 or IWGDF/IDSA grade 1 wound, and rarely neuropathic ulcerations. Tissue biopsy is known as the most standard method, and swab cultures are considered as not reliable since it generally includes the colonizers and not the causative pathogen [ 15 ]. But in this study, the swabs were obtained after a complete debridement in order to avoid the colonizers, and the CNS, as the main colonized organisms in the skin, were detected lower than 10% in this study, which showed that the swabs were reliable.…”
Section: Discussionmentioning
confidence: 99%
“…All the specimens were sampled to the microbiology laboratory within 48 h after hospital admission. Swabbing were collected from each wound after the wound had been cleansed (using 0.9% sterile saline and gauze) and debrided (removal of necrotic tissue, foreign material, calluses, and undermined wound edges) [ 15 ]. No antimicrobial agent or antiseptic was introduced into the wound before specimen collection.…”
Section: Methodsmentioning
confidence: 99%
“…Iodinated TG plays a crucial role in regulating TTF‐1 and PAX8. Our previous study showed that high iodinated TG in thyroid follicular lumen could inhibit the expression and transcription activities of TTF‐1 and PAX8 [Huang et al, ,, ], but the underlying mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study has shown significantly increased titer of thyroid autoantibodies after iodine supply in an iodine-deficient area, recent experimental studies showed the opposite results [ 53 55 ]. Two experimental studies have revealed that iodine in the thyroid gland regulates the expression of thyroid-specific proteins via negative feedback, indicating that restricted iodine intake would increase the expression of these specific proteins, enhance thyroid hormone synthesis, and lead to a more severe autoimmune response [ 54 , 55 ].…”
Section: Iodine Intake During Treatment Of Graves’ Diseasementioning
confidence: 99%